(untitled) (Revista Brasileira Multidisciplinar, 2022)
Research on the use of Building Information Modeling (BIM) has gained a lot of space lately. BIM technology brings numerous benefits to engineering projects through the integration of multidisciplinary data and the creation of detailed digital representations. For this reason, this work aimed to analyze the integration of BIM with Abaqus, Ansys, Robot and SAP2000 software, widely used for structural projects and numerical simulations. Therefore, a systematic literature review was performed in the Web of Science and Scopus databases, seeking articles that associated the term BIM with each software analyzed. A total of 30 articles were initially found and, after filtering them, 17 relevant articles remained, which were then analyzed and discussed one by one. After analyzing the articles, several benefits were found, however, gaps and limitations were also identified, showing the need for studies on the interoperability between BIM and structural software’s.